Prevalence and Risk Factors for Post-Traumatic Stress Reaction Among Resident Survivors of the Tsunami That Followed the Great East Japan Earthquake, March 11, 2011. (14th April 2016) - Matsubara, Chieko; Murakami, Hitoshi; Imai, Koubun; Mizoue, Tetsuya; Akashi, Hidechika; Miyoshi, Chiaki; Nakasa, Tamotsu
Abstract: Objective: The Great East Japan Earthquake triggered a massive tsunami that devastated the coasts of northern Japan on March 11, 2011. Despite the large number of "resident survivors, " who have continued to reside on the upper floors of damaged houses, few studies have examined the mental health of these residents. We explored the prevalence and risk factors of post-traumatic stress reaction (PTSR) among resident survivors. Methods: A cross-sectional household screening for health support needs was conducted among resident survivors in Higashi-Matsushima city, Miyagi, 2 to 4 months after the tsunami. Questions assessing PTSR were included in the screening interviews. Results: Of 5103 resident survivors, 5.7% experienced PTSR. PTSR risk factors, identified via regression analysis, differed according to the height of house flooding. When house flooding remained below the ground floor, PTSR was significantly associated with being female and regular psychotropic medication intake. These 2 factors in addition to being middle-aged or elderly and living alone were also risk factors when flood levels were above the ground floor. Conclusions: Following the tsunami, PTSR was found in a considerable number of resident survivors. Attention and support for people who use psychiatric medication, their families, and people living alone are suggested as possible directions for public health strategies. ( Disaster Med Public Health Preparedness . 2016;page 1 of 8)